Excessive reassurance seeking in depression versus obsessive-compulsive disorder: Cross-sectional and cognitive behavioural therapy treatment comparisons. (October 2020) - Katz, Danielle E.; Laposa, Judith M.; Rector, Neil A.
Highlights: Excessive reassurance seeking related to social attachment concerns higher in depression group compared to OCD group. CBT associated with significant reductions in excessive reassurance seeking in both OCD and depression. Reduction in reassurance seeking associated with symptom severity change in both groups. Intolerance of uncertainty significantly predicted change in reassurance seeking levels regardless of diagnosis. Abstract: Excessive reassurance seeking (ERS) has been hypothesized as an important maintenance factor in depression and obsessive compulsive disorder (OCD). The present study examined the types of ERS in depression and OCD, the effects of CBT on ERS, predictors of ERS reduction, and the relation between ERS reduction and symptom change. Method: Treatment-seeking participants diagnosed with a depressive disorder (N = 361) or OCD (N = 156) completed the Reassurance Seeking Scale (RSS) and symptom measures before and following CBT treatment. Measures of intolerance of uncertainty and distress tolerance were completed pre-treatment as potential predictors of ERS change. Results: Individuals with depression demonstrated higher pre-treatment ERS related to social attachment compared to those with OCD. ERS significantly decreased over treatment in both groups and change in ERS predicted symptom change among both OCD and depression groups. Higher pre-treatment intolerance of uncertainty significantly predicted less ERS change regardless of diagnosis. Distress tolerance was not associated with ERS changes. Conclusion: ERS is significantly related to symptom severity cross-sectionally as well as over treatment in depression and OCD, though types of ERS may differ. Higher intolerance of uncertainty may impede the reduction of ERS in CBT.